2005
DOI: 10.1002/pola.20699
|View full text |Cite
|
Sign up to set email alerts
|

New fluorinated thermoplastic elastomers. III. Novel method of synthesis and characterization of alternating fluorinated polyimide/fluorinated polyhybridsiloxane block copolymers via polycondensation

Abstract: The synthesis of fluorinated polyimide/fluorinated polyhybridsiloxane (FPI-FPHSX) block copolymers was achieved through the polycondensation of a,odichlorosilane fluorinated polyimides and a,o-disilanol fluorinated polyhybridsiloxanes. Three FPI-FPHSX block copolymers with 41, 50, and 76 wt % polyimide were synthesized and characterized by the tuning of the number-average molecular weight of the soft polyhybridsiloxane segments. The influence of the soft-segment length on the behavior of the thermoplastic elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…20 In another reports of theirs, 21 they used ,!-dichlorosilane fluorinated PI and ,!-disilanol polyhybridsiloxanes to synthesize fluorinated PI/ fluorinated polyhybridsiloxane block copolymers through a two-step polycondensation reaction. They observed phase separation in these fluorinated block copolymers.…”
mentioning
confidence: 99%
“…20 In another reports of theirs, 21 they used ,!-dichlorosilane fluorinated PI and ,!-disilanol polyhybridsiloxanes to synthesize fluorinated PI/ fluorinated polyhybridsiloxane block copolymers through a two-step polycondensation reaction. They observed phase separation in these fluorinated block copolymers.…”
mentioning
confidence: 99%
“…Proton nuclear magnetic resonance ( 1 H NMR) spectra were recorded on Bruker Avance 400 MHz spectrometer in dimethylsulfoxide (DMSO-d 6 ). The Proton resonances were designated as singlet (s) and multiplet (m).…”
Section: Equipmentsmentioning
confidence: 99%
“…[7][8][9][10][11] However, rubber properties had not been emphasized in these reports. Andre et al [7][8][9][10] reported a series of studies about fluorinated polysiloxane type TPE. They used allyl group telechelic PI moiety and various sized hydrosilane telechelic polyhybridsiloxane, through hydrosilylation reaction, to prepare a series of PI/polysiloxane alternating block copolymer TPE.…”
mentioning
confidence: 91%